2003
DOI: 10.1007/s00424-002-0950-6
|View full text |Cite
|
Sign up to set email alerts
|

The ClC-5 chloride channel knock-out mouse – an animal model for Dent's disease

Abstract: Mutations in the gene CLCN5 encoding the vesicular chloride channel ClC-5 lead to Dent's disease, an X-linked renal disorder. Dent's disease is characterised by proteinuria, hyperphosphaturia and hypercalciuria, which eventually lead to kidney stones and nephrocalcinosis. As it was unclear how mutations in a chloride channel might cause these symptoms, we and others have generated genetic mouse models to elucidate the underlying pathophysiological mechanisms. We review results obtained from these three mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
191
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 181 publications
(202 citation statements)
references
References 45 publications
(93 reference statements)
11
191
0
Order By: Relevance
“…A very similar phenotype is observed with the loss of Ostm1, an essential ␤-subunit of ClC-7 (21). Despite the belief that vesicular CLCs are generally involved in the acidification of intracellular organelles (22)(23)(24), lysosomal pH was normal in these KO mouse models (16,20,21). This observation led to the hypothesis (5) that these phenotypes are rather a consequence of impaired proton gradient-driven Cl Ϫ accumulation in those vesicles, similar to impaired nitrate accumulation in plant vacuoles that lack AtClC-a (7).…”
Section: Lysosomes Display 2clmentioning
confidence: 99%
See 1 more Smart Citation
“…A very similar phenotype is observed with the loss of Ostm1, an essential ␤-subunit of ClC-7 (21). Despite the belief that vesicular CLCs are generally involved in the acidification of intracellular organelles (22)(23)(24), lysosomal pH was normal in these KO mouse models (16,20,21). This observation led to the hypothesis (5) that these phenotypes are rather a consequence of impaired proton gradient-driven Cl Ϫ accumulation in those vesicles, similar to impaired nitrate accumulation in plant vacuoles that lack AtClC-a (7).…”
Section: Lysosomes Display 2clmentioning
confidence: 99%
“…These vesicular CLCs may provide counterion conductances for electrogenic proton pumping, thereby facilitating acidification of the respective compartment. Indeed, ClC-3, -4, and -5 have been shown to be required for proper acidification of endosomes (6,(22)(23)(24)41). The severe reduction in renal endocytosis observed with a loss of ClC-5 function may be attributed to reduced endosomal acidification (33) or Cl Ϫ accumulation (6).…”
mentioning
confidence: 99%
“…4B). Because other vesicular CLC proteins facilitate vesicular acidification (5,6,8), we determined the lysosomal pH of cultured hippocampal neurons by ratiometric fluorescence imaging (see Fig. 10, which is published as supporting information on the PNAS web site).…”
Section: Redistribution Of Late-endosomal͞lysosomal Markers and Lysosmentioning
confidence: 99%
“…In fact, ClC-4 and -5 function not as Cl Ϫ channels but as electrogenic Cl Ϫ ͞H ϩ exchangers (3,4). An impaired acidification of endosomes or synaptic vesicles was found in mice lacking ClC-3 (5, 6) or -5 (7,8). Probably as a consequence of defective endosomal acidification, the loss of ClC-5 leads to a stark reduction in proximal tubular endocytosis (7,9) and to human Dent's disease (10).…”
mentioning
confidence: 99%
“…ClC-5 is the first chloride channel for which a definitive role in the trafficking and acidification-dependent recycling of apical membrane proteins has been established (Gunther et al 1998;Devuyst et al 1999;Sakamoto et al 1999;Sayer and Simmons 2002). Animal models of knockout ClC-5 mice demonstrated that impairment of the endocytotic traffic is the major cause not only of tubular proteinuria but also of hypercalciuria and consequently kidney stones (Piwon et al 2000;Wang et al 2000;Gunther et al 2003). However, given the high interfamilial and intrafamilial phenotypic variability of DentÕs disease and its variants, it is conceivable that modifying genes could determine the phenotypic manifestation of the disease.…”
Section: Introductionmentioning
confidence: 99%